DEVELOPMENT OF AN AUTOMATED TECHNOLOGICAL LINE OF PRODUCTION OF FEED FOR LIVESTOCK WITH THE ADJUSTMENT THE QUALITY OF THE END PRODUCT: Array - and (Municipal economy of cities. Series: «Economy science», 2018)
The modes of operation of the electric drive of working machines in the agro-industrial complex are analyzed. A detailed substantiation of the properties of devices that are part of electromechanical systems is carried out and ways of adjusting efficiency of work on reduction of energy consumption are given. In scientific work, great importance was given to the mechanical characteristics of asynchronous motors and the properties of the converter as a receiver of electric energy. Using asynchronous electric drive is proved, in practice, it is possible to reduce losses in the unregulated speed of the engine and in the feed line, thus reducing the voltage on the engine shaft, using reactive power compensation. The article presented in the review reviews the main modes of operation of the electric drive of working machines in the agro-industrial complex. A detailed substantiation of the properties of the devices that are part of the electromechanical systems is carried out and ways of adjusting the efficiency of work on reducing energy consumption are given. The analysis of the main methods of energy saving in the electric drives of the agro-industrial complex is carried out, which allows changing at the moment the supply to the working body of the required power with minimal losses. A structured system of frequency converter asynchronous motor with short-circuit rotor, which shows the detailed connection of the converter to the electric drive, is a promising technical solution of the modern regulated electric drive in the coming years. The results of numerical calculations of the parameters of the energy process of transport of energy from the source to the consumer are obtained, which may be useful in the development and implementation of modern efficient energy saving control algorithms. Studies have shown that replacing unladen electric motors in the agroindustrial complex with engines of lower power yelds significant electricity savings. Keywords: electric drive, energy saving, frequency converter, productivity, regulation, energy efficiency.